2020
DOI: 10.3389/fpsyg.2020.00273
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions in Measuring Teaching Behavior Across Six Countries: A Multi-Group Confirmatory Factor Analysis Approach to Measurement Invariance

Abstract: The purpose of this study is to examine measurement invariance of scoring of teaching behavior, as perceived by students, across six cultural contexts (Netherlands, Spain, Turkey, South Africa, South Korea, and Indonesia). It also aims to compare perceived teaching behavior across the six countries based on a uniform student measure. Results from multi-group confirmatory factor analyses (MGCFA) showed perceived teaching behavior in the six countries to be adequately invariant. Perceived teaching behavior was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 71 publications
(96 reference statements)
1
19
0
2
Order By: Relevance
“…In addition, scientific studies measuring observed teaching quality involving multiple countries are currently not present, especially in the context of secondary education (cf. André et al, 2020;Fischer et al, 2019). This study is among the first to address this gap.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, scientific studies measuring observed teaching quality involving multiple countries are currently not present, especially in the context of secondary education (cf. André et al, 2020;Fischer et al, 2019). This study is among the first to address this gap.…”
Section: Introductionmentioning
confidence: 94%
“…These studies report evidence of partial-invariance between countries. More specific, André et al (2020) and Scherer et al (2016) found evidence supporting (partial) metric invariance but no support for scalar invariance. Both studies applied the Multiple Group Confirmatory Factor Analysis (MGCFA) method which is rooted in the factor analysis framework.…”
Section: Introductionmentioning
confidence: 90%
“…Notable exceptions are the studies by André et al (2020) and Scherer et al (2016). These studies report evidence of partial-invariance between countries.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Table 1 details the conceptualizations of each domain. Several studies from different countries provide evidence suggesting that the items included in the ICALT and My Teacher questionnaire cluster according to these six domains (André et al, 2020;Maulana & Helms-Lorenz, 2016;van de Grift et al, 2011). • Efficient classroom management An efficient classroom management is structured by clear procedures, routines, and rules about where and how learning takes place.…”
Section: Instructional Effectivenessmentioning
confidence: 99%